Control of Molecular Catalysts for Oxygen Reduction by Variation of pH and Functional Groups. Issue 8 (17th March 2021) - Friedman, Ariel; Reddy Samala, Nagaprasad; Honig, Hilah C.; Tasior, Mariusz; Gryko, Daniel T.; Elbaz, Lior; Grinberg, Ilya
Abstract: In the search for replacement of the platinum‐based catalysts for fuel cells, MN4 molecular catalysts based on abundant transition metals play a crucial role in modeling and investigation of the influence of the environment near the active site in platinum‐group metal‐free (PGM‐free) oxygen reduction reaction (ORR) catalysts. To understand how the ORR activity of molecular catalysts can be controlled by the active site structure through modification by the pH and substituent functional groups, the change of the ORR onset potential and the electron number in a broad pH range was examined for three different metallocorroles. Experiments revealed a switch between two different ORR mechanisms and a change from 2e − to 4e − pathway in the pH range of 3.5‐6. This phenomenon was shown by density functional theory (DFT) calculations to be related to the protonation of the nitrogen atoms and carboxylic acid groups on the corroles indicated by the p K a values of the protonation sites in the vicinity of the ORR active sites. Control of the electron‐withdrawing nature of these groups characterized by the p K a values could switch the ORR from the H + to e − rate‐determining step mechanisms and from 2e − to 4e − ORR pathways and also controlled the durability of the corrole catalysts. The results suggest that protonation of the nitrogen atoms plays a vital role in both the ORR activity and durability for these materials and that p K a of the N atoms at the active sites can be used as a descriptor for the design of high‐performance, durable PGM‐free catalysts. Abstract : ORR tuning : Oxygen reduction reaction (ORR) activity, durability, and other features of platinum‐group metal‐free molecular catalysts are strongly influenced by the protonation degree of the nitrogen atoms surrounding the metal center. By changing the substituents, it is possible to tune the p K a of those N atoms and by that to control the catalyst properties. To investigate this, three different corroles are used as a model, and their performance at different pH values is tested.